Intervención fisioterapéutica en la prevención de complicaciones respiratorias en adultos con esclerosis lateral amiotrófica - Antonella Nicole, Viteri Sanclemente (2022)
ABSTRACT: The present research project was oriented to the investigation of bibliographic data, preferably in scientifically recognized clinical trials on physiotherapeutic intervention in the prevention of respiratory complications in adults with amyotrophic lateral sclerosis, through an updated compilation of scientific databases of high impact. For the development of the project, the bibliographic search consisted of the compilation of 85 scientific articles, all of which were analyzed applying the inclusion and exclusion criteria, subsequently qualified using the Physiotherapy Evidence Database (PEDro) methodological evaluation scale. with a score equal to or greater than six, from this result 35 scientific articles were obtained in English and converted to Spanish. The scientific databases used were PubMed, Elseiver, Scientific Journals Rankings (SJR), Scientific Reports and Physiotherapy Evidence Database (PEDro). With articles in the timeline from 2016 to 2021 in a total of 34 articles, and due to the scarcity of referring clinical trials, one corresponding to the year 2012 was taken. In the results obtained from the research and analysis of clinical trials, it is evident that various authors promote physical activity in Amyotrophic Lateral Sclerosis (ALS) for the preservation of vital functions, both physical and respiratory, to form a single group considering that the training of the entire respiratory musculature promotes that the respiratory muscles also carry out the inspiration and expiration process correctly, affirming that therapeutic exercise added to respiratory therapy can prevent respiratory complications if treated early, complemented with dosed and individualized training and proper management of secretions. Keywords: Amyotrophic lateral sclerosis, respiratory complications, therapeutic exercise, respiratory therapy